Leveraging Process Management for Strategic Change and Organizational Learning in Industry 4.0 - Jamshaid Iqbal Janjua; Imran Asghar Warraich; Qasim Abbas; Nadeem Sarwar (Dialogue Social Science Review (DSSR), 2025)
In this article, we examine how effective process management (PM) in I4.0 is distinguished by its ability to integrate human resources (HR) and operational processes towards a strategic goal and organizational configuration, within the context of achieving competitive advantage. This research focused on small- and medium-sized enterprises (SMEs) in the manufacturing and service industries in Mexico. We surveyed firms with the help of a simple random sampling method, and we received responses that we could use. Three levels of data analysis were performed: descriptive statistical analysis for the participating companies and respondents’, confirmatory factor analysis for the measurement models to test if they fitted the data, and causal analysis to determine the hypothesised relationships between constructs. The findings indicate that PM contributes to the implementation of I4.0 in a systemic way as a critical mediator. In this article, the author attempts to identify three central objectives in the process of adopting I4.0: strategic enhancement, competitiveness, and organisational integration. PM has significant effects on these objectives, which are accomplished through two primary functions: HR and operations. This paper emphasizes the role of I4.0 PM in the digital transformation of SMEs and ensures HR and operations are leveraged to enable strategic change, organizational learning, and enhanced competitiveness.